MODEL OF MEDIATOR COMMUNICATION IN INTERPERSONAL RELATIONSHIP OF MARRIED COUPLES THROUGH TA'ARUF PROCESS IN PALU CITY - SUMARNI ZAINUDDIN; MAHPUDDIN; ISRAWATY SURIADY (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
This study aims to identify and provide an overview related to the mediator communication model in the interpersonal relationships of married couples through the ta'aruf process in Palu City.The research method uses qualitative types. Data collection techniques are in-depth interviews (in-depth interview) and direct observation. For analytical techniques using Data Reduction, Data Presentation, and Conclusion Drawing/Verification. The results showed that the mediator's communication model in Islamic marriages through ta'aruf process in Palu City consisted of (a) Asking marriage readiness. The mediator will ask the brothers and sisters related to their readiness to marry in Islam through the ta'aruf process, (b) Self Biodata. For brothers and sisters who are ready to get married are required to write their data consisting of name, height, profession/occupation, number of siblings to the illness, (c) Face-to-face communication is divided into two stages (1) Introduction. Both of them can only convey messages through a dividing barrier like a curtain, but if they feel comfortable, the mediator allows the brothers to see the face of the sisters even though veiled and can communicate directly, and (2) Applying. In this process, the cleric as a mediator has the role of providing enlightenment to the woman's family or parents regarding Islamic marriage so that it is not complicated and (d) Advice. Before getting married, the cleric as a mediator first gives marriage advice, such as maintaining prayer time prayers and other worship, not being selfish, responsible based on the role of husband and wife, and the most important thing is not having an affair.